Penggunaan Na2O/Fly Ash Sebagai Katalis Pada Tahap Transesterifikasi Minyak Sawit Off-Grade Menjadi Biodiesel - Jhon Fery Marihot Tua S; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel production from the vegetable oil using homogenous catalyst has disadvantage in the product separation and negative environmental impact. Biodiesel synthesis from off-grade palm oil using Na2O/Fly ash solid base catalyst is good to simplify the separation process and the utilization of fly ash as palm oil mill waste tp support the Na2O basic site. Biodiesel production aims in this study is to see the influence of reaction temperature, molar ratio of methanol and oil and concentration of Na2O/fly ash towards biodiesel yield. The process was conducted through reaction of esterification and followed by transesterification reaction. Processing of the data in this study was conducted by response surface methodology (RSM) using Design Expert 7.0 program which is experimental design determined by central composite design (CCD) which consists of three variables. The highest result of biodiesel yield was 77,33% at 60oC reaction temperature, molar ratio of methanol : oil 8 : 1 and catalyst concentration of Na2O/fly ash 4%-w. Biodiesel characteristics like as density, kinematic viscosity, acid value and flash point has been appropriate by Indonesian biodiesel standard. The most significant process condition affecting the yield of biodiesel was catalyst concentration.Keywords: biodiesel, fly ash, off-grade palm oil, solid base catalyst